"It's Real, It's Much More Real": An Exploration of Values Based Reflective Practice® as a Reflective Tool. (28th January 2022) - Kennedy, Heather; Kennedy, Jennifer
Abstract : Values Based Reflective Practice (VBRP®) is a group reflection framework widely utilized within healthcare settings across Scotland, where groups of colleagues meet and discuss their workplace-based experiences using the VBRP® structure. The VBRP® model has previously been noted within HSCC as assisting "courageous conversations" about working in a caring vocation (Bunniss, 2021a, 2021b). Despite its national platform, however, there has been limited evaluation of VBRP®. Aim: This study explores the impact of VBRP® as a reflective tool among undergraduate medical students. Method: A qualitative action research methodology was used. Results: Three themes were identified from the data: overcoming barriers to reflection during VBRP®; enhancing reflection through the social nature of VBRP®; participants' perceptions of reflection through the lens of VBRP®. Conclusion: VBRP® enabled deeper, more authentic reflection and enhanced written reflection abilities due to its social nature. It promoted the formation of peer support networks and positive coping mechanisms among medical students. Teamworking and group relationships were also improved.